The Influence Of Return On Assets, Earnings Per Share And Debt To Assets Ratio On Stock Prices In Lq 45 Companies Listed On The Indonesian Stock Exchange - Khoiriyah, Ila Atul; Rosyidi, Syaiko (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This research aims to determine, for the years 2018–2022, how ROA, EPS, and the debt-to-assets ratio relate to the stock prices of 45 businesses traded on the Indonesia Stock Exchange. Stock prices are used as the dependent variable in this study, while debt-to-assets ratio, return on assets, and earnings per share are used as the independent factors. For the years 2018–2022, 45 LQ-listed firms on the Indonesia Stock Exchange will make up the population. Procedures for data collection in research projects using the documentation approach. On the other hand, purposive sampling is the technique used to pick the samples. Out of a total of 18 businesses, 90 were included in the research cohort. The multiple linear regression analysis approach was used to analyse the data. By running the prior regression through the standard assumption test, we were able to extract the BLUE (Best Linear Unbiased Estimate) data. Hypothesis testing has shown that ROA has a statistically significant negative effect. While Earnings per Share has a little but beneficial effect, the Debt to Assets Ratio has a tiny but negative effect.